INTRODUCTION APPLICATION OF INDONESIA PRESIDENTIAL PALACE USING MACROMEDIA DREAMWEAVER MX - Ade Jaja Badruzaman; Ristyawati Ristyawati, SKom., MMSI (Jurnal Sistem Informasi, 2007)
At this writing the introduction discussed the application of the Republic of IndonesiaPresidential Palace using Macromedia Dreamweaver MX. This application is madewith the purpose of providing information to the public in order to know the history,functions and building what is the Presidential Palace environment. Indonesia hasrecorded five of the presidential palace: Palace Jakarta, Bogor Palace in Bogor,Cipanas in Cipanas Palace, Palace and Sukawati Bali Gedung Agung Palace inYogyakarta. From history, the Merdeka Palace, Istana Negara, Gedung Agung,Cipanas Palace, and the Bogor Palace was built during the Dutch East Indiesgovernment. Tampaksiring palace built during President Sukarno. Presidential Palaceis part of a historic building in Indonesia. Perhaps many people will not know thehistory of the Presidential Palace. With this application the public expected to knowsome of the history of this nation.